A Philosophical Analysis of the Implementation of Vision, Mission, Strategies, and Goals of Junior High Schools to Improve Education Quality - Siti Robiah; Wandani; Neni Sri Rahayu; Rina Widaystuti (South Sulawesi Education Development (SSED), 2024)
A school's vision, mission, strategy, and goals are key elements in designing and managing quality education, especially when based on strong philosophical values. All these elements, when based on philosophical values, form a strong foundation for quality education development. These values include ethical principles, morality, and philosophical beliefs that guide every decision and action in the educational context. By having a strong foundation of values, schools can create a learning environment of integrity, inclusiveness, and character-building for students by their educational vision and mission. The purpose of the research is to explore deeper information about the implementation of the school's vision, mission, and strategy to improve the quality of education based on philosophical values. The object of this research is SMPN 2 Margahayu and MTs Al Ihsan Baleendah, Bandung Regency. The method used is a qualitative approach with a case study method. In line with the case study research design, the data collection techniques used were interviews and documentation. The data analysis technique used is category analysis, which this technique groups data into categories or classifications to identify related patterns or variables. The results of this study show that in preparing the vision, mission, strategies, and goals of both schools, there are efforts to improve the quality of education. In addition, the vision, mission, strategies, and goals of the two schools contain philosophical values that are the objectives of national education.